Non-Muslims in the early Islamic Empire from surrender to coexistence - Levy-Rubin, Milka (Cambridge studies in Islamic civilization, 2011)
The Muslim conquest of the East in the seventh century entailed the subjugation of Christians, Jews, Zoroastrians, and others. Milka Levy-Rubin's remarkable book traces the emergence of these regulations from the first surrender agreements in the immediate aftermath of conquest to the formation of the canonic document called the Pact of Ụmar, which was formalized under the early Ạbbasids, in the first half of the ninth century.